PENGEMBANGAN WARISAN BUDAYA TRADISIONAL MENUJU EKOWISATA DUSUN GIYANTI WONOSOBO - Puspitawati, Yenny; Sabardila, Atiqa (Universitas Muhammadiyah Surakarta, 2021)
This study aims to (1) describe the model development of Giyanti village’s traditional cultural heritage, and (2) how it elaborates the community and the government in developing the ecotourism of Giyanti Hamlet. This research is a qualitative research. Methods of the data collection in the field is by using observation techniques, interviews, and documentation. The collected data were then analyzed by describing the results of the study in detail and systematic. Then, the results are presented informally, namely the formulation with ordinary words in the form of narrative texts. In this study, it is argued that the development of culture towards the ecotourism of the Giyanti village was wrapped in the Community Based Tourism model, which was able to elevate the culture, social, economy of the local community. However, full participation from the community is not enough if there is no good colaboration with the government. Therefore, there must be a good colaboration between the community and the government as the organizer of the ecotourism in the village of Giyanti, Wonosobo Regency.